Performance evaluation of corner effect in UMTS / Nurzaliza Ghazali - Ghazali, Nurzaliza (2009)
In cellular network such as UMTS, corner effect is one of the problem that effected the performance evaluation of handover algorithms. Handover is one of the key functionalities which tries to keep a user equipment (UE) connected to the best base station (Node B). Handover is on the downlink received signal strength (RSS) and carrier-to-interference ratio (CIR) measurements. This paper determines the comer effect at three location of urban area. Parameter of Ee/No (dB) is considered to evaluate the quality of services of the system. Meanwhile, parameter RSCP is used to measure the percentage of signal dropped. The NEMO ANALYZE software is used in this project to analyze the measurement at selected route. The actual data of Ee/No and RSCP was obtained from drive test measurements. Hence, the comparison between three location was done to determine the worst route that had been effected by the corner effect environment.